A COMPARATIVE ANALYSIS OF APPROACHES TO THE DEFINITION OF USER INTEREST TO LEARNING MATERIALS IN ADAPTIVE LEARNING SYSTEMS - Артамонов, Є. Б. (Science-based technologies, 2016)
This article considers the problem of approaches to automatically definition of the interest rate to elements of e-learning systems. Interest rate is used as one of the key parameters that characterize the quality of the perception of educational material if you are working without the direct feedback from the teacher. Based on the assessment of the quality of perception and a number of other options can be adaptive formation of information resources that will automatically build a flexible system of e-learning system content. The main problem of assessment interest is as follows: 1) the lack of ready mathematical models describing the relationship interest and users reactions to educational materials, 2) the absence of a statistical sample of the evaluation relations material-interest- student, 3) some of the parameters of the user reactions estimates are non-numeric character. The article presents a comparative analysis of the following methods: Bayes, the phase interval, of logical inference, neural networks, fuzzy sets. It is shown that the fuzzy logic is the most perspective mathematical apparatus to develop a system of determining the interest rate of user in learning materials.